Two Kitchens and Other ‘Modern’ Stories: Rethinking the Family in Contemporary Nepal Through Household Conflict and Fission (HIMALAYA, 2022)
This paper examines the ongoing phenomenon of household nuclearization in the Newar city of Bhaktapur, Nepal. Building upon 15 months of ethnographic research conducted in 2018–19 among middle-class families, I investigate the reasons for household fission and the related kinship transformations. Tracing the interconnected stories of conflict and dispersal of the members of a joint family, I argue that transitions in domestic structures not only represent the consequence of improved economic possibilities but also communicate dramatic social transformations and a redefinition of hierarchies of value and power between family members, which emerge alongside new ideas of family and self. By negotiating domestic spaces and practices, householders redefine a modern dharma to attain a middle class ideal of relatedness. By considering the domestic as the locus of the negotiations between social change and continuity, and by looking at conflict as a dialogical process of cultural revision, this study provides a new perspective on the making of moral modernities in Nepal, ultimately contributing to recent debates in the fields of kinship studies, anthropology of conflict, and moral anthropology.